A Wide-Bandwidth Monopolar Patch Antenna with Dual-Ring Couplers - Yuanyuan Zhang; Juhua Liu; Zhixi Liang; Yunliang Long (International Journal of Antennas and Propagation)
A new center-fed circular patch antenna with two coupled annular rings is presented. When the two annular rings are coupled properly, a wide band from 5.45 GHz to 7.16 GHz is achieved with a monopole-like radiation pattern. Measured results show that the antenna with a low profile of 0.027 wavelengths (at 5.45 GHz) has a bandwidth of 27.1% and a measured maximum gain of 6 dBi. The radiation pattern is omnidirectional and remains relatively stable within the operating band.